Pemikiran Thomas Aquinas: Relevansi Pendidikan Spiritual dan Moral Aquinas dengan Pendidikan Islam di Tengah Era Disrupsi - Muhamad Basyrul Muvid (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2021)
Globalization gave birth to a new paradigm for human life that gave rise to both negative and positive sides. Most of them are trapped in the negative side of globalization. The negative paradigms are liberalism, secularism, individualism, materialism, hedonism which causes humans to be far from the spirit of religion and norms. Finally, he experienced a drought; spiritual and moral crisis that has an impact on his social life. The purpose of this study is to analyze the thoughts of Thomas Aquinas, who is a famous realist philosophy figure about spiritual and moral education as a solution to the problems of society in the era of disruption and its relevance to Islamic education. Aquinas' spiritual education is a process to educate people to know their God by optimizing their minds through the meaning of the five paths offered by Aquinas. Then, Aquinas' moral education is the process of forming behavior in accordance with God's instructions as an effort to achieve true happiness by always emphasizing actions that are in accordance with God's norms. The relevance of Aquinas' spiritual and moral education with Islamic education is that Islamic education is also a process to educate people to become obedient individuals to God and individuals who uphold moral values ​​for their social life. Spiritual and moral aspects are a priority in Islamic education in addition to the knowledge aspect.